QuantiFERON-TB Gold Plus Assay Specificity in Children and Adolescents With Suspected Tuberculosis—A Multicenter Cross-sectional Study in Spain. Issue 9 (22nd July 2021) - Soler-Garcia, Aleix; Gamell, Anna; Santiago, Begoña; Monsonís, Manuel; Cobo-Vázquez, Elvira; Bustillo-Alonso, Matilde; Tagarro, Alfredo; Pérez-Gorricho, Beatriz; Espiau, María; Piqueras, Ana Isabel; Korta-Murua, José Javier; Rodríguez-Molino, Paula; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : In this cross-sectional study of 284 children and adolescents with clinically or radiologically suspected tuberculosis in a low-endemic country, the QuantiFERON-TB Gold Plus assay specificity, sensitivity, positive predictive value and negative predictive value were 91.5%, 87.3%, 86.4%, and 91.2%, respectively. The specificity was higher than that observed in tuberculin skin tests performed simultaneously, but similar to previous-generation interferon-gamma release assays.